Bleeding battle in soft tissue sarcoma surgery: a review of perioperative considerations and management - Goh, Eyrique Boay Heong; Paul, A. G.; Looi, Collin Seng Kim (Manipal Alumni Association Malaysia, 2021)
Bleeding is a common expected complication during surgery, but more so in advanced sarcoma resection surgery owing to the tumour’s angiogenesis. As surgery is potentially curative for primary nonmetastatic extremity soft tissue sarcoma – hence surgery is necessitated. In this case, we have a patient with significant bleeding intraoperatively requiring several methods and techniques to control the hemorrhage. The management of bleeding involves multiple assessment and strategies to ensure appropriate care for the patients. The management is perioperative involving all stages: preoperative risk identification and optimization to intraoperative surgical options and techniques to postoperative care. The objective of this review is to establish a guideline on factors and options that surgeons should to be aware, going into surgery from preoperative to postoperative management when bleeding ensues. Latest updates and recent evidence help ensure improved clinical management for sarcoma patients undergoing surgery.